Ten Minutes to Live - Micheaux, Oscar; Lang, Lester; Chenault, Lawrence; Guilford, Willor Lee; Tucker, Lorenzo (bfi, 2016)
The conversion to sound pictures, with 1931's "The Exile", was not an easy one for director Micheaux, but the director's motto of "Got to keep going!", recorded by biographer Patrick McGilligan, is undoubtedly evident in this Harlem-set sound production of 1932. Based on three (unpublished) short stories by the director, the various strands of this anthology film of "Harlem Life" - including a "renowned" director's attempt to "recruit" a female performer, the (attempted) violent revenge of a spurned woman tricked into a sham marriage, and a concluding melodrama involving an ill-starred romance between a young woman and an escaped convict - come together at the fictional "Club Lybia", where dancers, musical performers, and vaudeville acts from the real-life Cotton Club and Connie's Inn are recorded for all posterity. Yes, a discerning viewer may object to the stagy blocking, the overwritten dialogue, the charitably "amateur" performances, and, most glaringly, the director's once-audible cry of "Cut!", but what these independent, hard-scrabble productions lack in resources and technical proficiency they more than make up for in portraying a side of American life almost entirely ignored by mainstream Hollywood. [www.zekefilm.org]